Correlation of AMH with cardiometabolic markers in polycystic ovarian syndrome: Systematic review and meta-analysis - Saloni Kamboj; Spondita Banerjee; Gita Das; Smit Thakkar; Rohith Atluri; Shruti Shivakumar; Heena D Tiwari (Wolters Kluwer Medknow Publications, 2024)
Objective: The purpose of this systematic review and meta-analysis was to determine whether there is a connection between polycystic ovarian syndrome (PCOS)-affected women's levels of the anti-Mullerian hormone (AMH) and certain cardiometabolic indicators. Materials and Methods: To find pertinent recent research published between 2017 and 2023, a thorough search was done in PubMed. Studies were included if they looked into the relationship between PCOS-related women's AMH levels and cardiometabolic markers. To determine pooled effect estimates, data from the included studies were examined using random-effects models. Results: Five papers were included in the meta-analysis since they satisfied the inclusion requirements. The meta-analysis found substantial positive relationships between AMH levels and markers of insulin resistance, fasting blood sugar levels, and dyslipidemia measures such as total cholesterol (SMD: 0.68, 95% confidence interval: 0.34-1.00, P < 0.001). Conclusion: This systematic review and meta-analysis show that AMH levels in PCOS-affected women significantly positively correlate with markers of insulin resistance, fasting glucose levels, and dyslipidemia parameters. These findings imply that the pathogenesis of the cardiometabolic abnormalities seen in PCOS may include AMH. AMH may be used as a biomarker to estimate the cardiometabolic risk in PCOS-affected women, but more studies are required to determine its clinical applicability.